2022
DOI: 10.1111/mms.12923
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal fin mark changes for assigning sexes to individual bottlenose dolphins, Tursiops truncatus

Abstract: . Sexing cetaceans typically requires extended periods of observation or expensive molecular methods. An alternative approach using photo‐identification may provide a cost‐effective, noninvasive method for assigning a sex to free‐ranging individuals. We investigated two methods for predicting the sex of common bottlenose dolphins (Tursiops truncatus) from Namibia, using the rate of change in dorsal fin (1) trailing edge marks or (2) surface features (scarring and lesions) and binary logistic regression models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Variables included fin shape, scarring and nicks, and epidermal lesions with scarring being one of the most important predictors of sex. Several recent studies on other species validated the reliability of using tooth rake marks as an indicator of sex (e.g., Cuvier's beaked whales, Ziphius cavirostris; Coomber et al, 2016; Indo-Pacific humpback dolphins, S. chinensis; Wright et al, 2017; Australian humpback dolphins, S. sahulensis; Brown et al, 2016; common bottlenose dolphins, T. truncatus; James et al, 2022). A previous study of sexual dimorphism in common bottlenose dolphins revealed that the number of scars but not the surface covered by scars was higher in males than in females (Tolley et al, 1995), showing the need to test different parameters to find the one(s) best predicting the sex of dolphins for each species or even each population.…”
mentioning
confidence: 98%
“…Variables included fin shape, scarring and nicks, and epidermal lesions with scarring being one of the most important predictors of sex. Several recent studies on other species validated the reliability of using tooth rake marks as an indicator of sex (e.g., Cuvier's beaked whales, Ziphius cavirostris; Coomber et al, 2016; Indo-Pacific humpback dolphins, S. chinensis; Wright et al, 2017; Australian humpback dolphins, S. sahulensis; Brown et al, 2016; common bottlenose dolphins, T. truncatus; James et al, 2022). A previous study of sexual dimorphism in common bottlenose dolphins revealed that the number of scars but not the surface covered by scars was higher in males than in females (Tolley et al, 1995), showing the need to test different parameters to find the one(s) best predicting the sex of dolphins for each species or even each population.…”
mentioning
confidence: 98%